2018
DOI: 10.7717/peerj.5485
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal shifts in the diet of the barnacle Amphibalanus eburneus within a subtropical estuary

Abstract: The success of many sessile invertebrates in marine benthic communities is linked to their ability to efficiently remove suspended organic matter from the surrounding water column. To investigate the diet of the barnacle Amphibalanus eburneus, a dominant suspension feeder within the Indian River Lagoon (IRL) of central Florida, we compared the stable isotopes ratios (δ13C and δ15N) of barnacle tissue to those of particulate organic matter (POM). Collections were carried out quarterly for a year from 29 permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Importantly, our results indicate that no single species can do it all, and diverse assemblages of filter feeders may amplify the ecosystem services provided by these organisms in estuarine systems. Additional work is needed to investigate the role of other epifaunal and benthic filter feeders that are currently dominant members of these communities within the IRL (Freeman et al 2018;Janiak et al 2018). Our results indicate that bloom-forming algal species in the IRL can be cleared and assimilated by resident bivalves and that restoring healthy populations of native filter feeding species may aid in the mitigation or prevention of harmful algae blooms in coastal waters.…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, our results indicate that no single species can do it all, and diverse assemblages of filter feeders may amplify the ecosystem services provided by these organisms in estuarine systems. Additional work is needed to investigate the role of other epifaunal and benthic filter feeders that are currently dominant members of these communities within the IRL (Freeman et al 2018;Janiak et al 2018). Our results indicate that bloom-forming algal species in the IRL can be cleared and assimilated by resident bivalves and that restoring healthy populations of native filter feeding species may aid in the mitigation or prevention of harmful algae blooms in coastal waters.…”
Section: Discussionmentioning
confidence: 87%
“…These infaunal communities therefore represent complex food webs with different allochthonous and autochthonous sources of nutrients being assimilated and ultimately passed on to other infaunal or pelagic predators (Abreu et al, 2006;Galván et al, 2008). In addition, elevated δ 15 N values of POM, SOM, individual species, and functional groups at site I12 suggest the presence of anthropogenic nutrient inputs from nearby human development and highlight the potential use of infaunal organisms (in addition to epifauna) as sentinel species for nutrient pollution in the IRL (Freeman et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…These sites (herein termed I11 and I12 for NIRL 11 and NIRL12, respectively) were chosen because preliminary work at nearby locations showed that they differed in their benthic cover, with sparse coverage of the seagrass Halodule wrightii and high levels of benthic detritus at I11 and bare sediment and low levels of detritus at I12. In addition, although the locations were within approximately 4 km of each other, I12 was closer to chronic human impact and potential nutrient inputs from development around the city of Titusville, FL (Freeman et al, 2018); I11, in contrast, was on the east side of the lagoon adjacent to restricted, conservation land that is part of the Kennedy Space Center. We thus predicted that the composition of food sources [e.g., particulate organic matter (POM) suspended in the water column and deposited on the surface of the sediment] would differ at these two sites and that their varying proximity to human development would influence the baseline isotopic signal of the site (in particular for δ 15 N; Freeman et al, 2018).…”
Section: Isotopesmentioning
confidence: 99%
See 2 more Smart Citations